Identification of Burkholderia pseudomallei Near-Neighbor Species in the Northern Territory of Australia. - Jennifer L Ginther; Mark Mayo; Stephanie D Warrington; Mirjam Kaestli; Travis Mullins; David M Wagner; Bart J Currie; Apichai Tuanyok; Paul Keim (PLoS Neglected Tropical Diseases, 2015)
Identification and characterization of near-neighbor species are critical to the development of robust molecular diagnostic tools for biothreat agents. One such agent, Burkholderia pseudomallei, a soil bacterium and the causative agent of melioidosis, is lacking in this area because of its genomic diversity and widespread geographic distribution. The Burkholderia genus contains over 60 species and occupies a large range of environments including soil, plants, rhizospheres, water, animals and humans. The identification of novel species in new locations necessitates the need to identify the true global distribution of Burkholderia species, especially the members that are closely related to B. pseudomallei. In our current study, we used the Burkholderia-specific recA sequencing assay to analyze environmental samples from the Darwin region in the Northern Territory of Australia where melioidosis is endemic. Burkholderia recA PCR negative samples were further characterized using 16s rRNA sequencing for species identification. Phylogenetic analysis demonstrated that over 70% of the bacterial isolates were identified as B. ubonensis indicating that this species is common in the soil where B. pseudomallei is endemic. Bayesian phylogenetic analysis reveals many novel branches within the B. cepacia complex, one novel B. oklahomensis-like species, and one novel branch containing one isolate that is distinct from all other samples on the phylogenetic tree. During the analysis with recA sequencing, we discovered 2 single nucleotide polymorphisms in the reverse priming region of B. oklahomensis. A degenerate primer was developed and is proposed for future use. We conclude that the recA sequencing technique is an effective tool to classify Burkholderia and identify soil organisms in a melioidosis endemic area.